Les Actes de Marc en éthiopien: remarques philologiques et histoire de la tradition - Lusini, Gianfrancesco (Apocrypha, 2002)
Among the Ethiopic manuscripts entrusted by Ferdinando Martini (1841-1928) to the Biblioteca Forteguerriana of Pistoia (G. Lusini, I manoscritti etiopici del Fondo Martini nella Biblioteca Forteguerriana di Pistoia, «Æthiopica», V, 2002, 156-175), a hagiographic and homiletic collection dating from the XVIIIth-XIXth C. (Ms. Martini etiop. no. 5 = Zanutto no. 2) bears the second witness of the Acts of Marc translated directly from a Greek model (ff. 82r-89r). This re-censio antiqua of the Passio Marci (M. Geerard, Clavis Apocryphorum Novi Testamenti, Turnhout, Brepols, 1992, 179-181, no. 287) is different from the text transmitetd as a section in the apocryphal collection of the Acta apostolorum (Gadla h. awaryat), translated from Arabic in the XIVth c. A comparison between the manuscript in Pistoia and the one previously known (EMML 1763, ff. 224r-227r, dating from 1336/37 or 1339/40), allows one to appreciate the value of the Ethiopic version, reflecting an ancient phase of the Greek tradition (preceding the one attested by the manuscripts) and driving to some considerations about the Ethiopic texts with "double" re-censions (from Greek and from Arabic).